Extensions of barrier sets to nonzero roots of the matching polynomial - Ku, C.Y.; Wong, K.B. (Elsevier, 2010)
In matching theory, barrier sets (also known as Tutte sets) have been studied extensively due to their connection to maximum matchings in a graph. For a root theta of the matching polynomial, we define theta-barrier and theta-extreme sets. We prove a generalized Berge-Tutte formula and give a characterization for the set of all theta-special vertices in a graph. (C) 2010 Elsevier B.V. All rights reserved.